Pengaruh karakteristik individu dan kepuasan kerja terhadap Organizational Citizenship Behavior (OCB) perawat dengan komitmen organisasi sebagai variabel intervening - Ismuhadi Ismuhadi; Yusmahdi Yusmahdi (Holistik Jurnal Kesehatan, 2021)
Individual characteristics, Job satisfaction of hospital nurse Organizational Citizenship Behavior (OCB) with Organizational Commitments as Intervening Variable Background: A hospital organization supported by competent nurses encourages the creation of the best services from the hospital. Work in a hospital could flexible by individually and in a team, competent nurses can work professionally in hospitals and must be able to work in Organizational Citizenship Behavior (OCB) as well.Purpose: To determine Individual characteristics, Job satisfaction of hospital nurse organizational citizenship behavior (OCB) with Organizational Commitments as Intervening VariableMethod: An analysis of the research with a structural equation model, at the Cut Meutia Lhokseumawe Hospital in North Aceh with a total sample of 120 nurses using simple random sampling method.Results: Finding that individual characteristics and job satisfaction have a significant effect on organizational commitment, individual characteristics and job satisfaction and organizational commitment have a significant effect on OCB. The role of organizational commitment as an intervening variable mediates the relationship between individual characteristics and job satisfaction with OCB.Keywords: Individual characteristics; Job satisfaction; Hospital; Nurse; Organizational Citizenship Behavior (OCB) Pendahuluan: Organisasi rumah sakit sangat membutuhkan perawat yang bersedia melakukan lebih dari sekadar tugas rutinitas yang diberikan oleh pimpinan, sikap kerelaan perawat bersedia membantu perawat lain adalah sikap yang sangat menguntung organisasi. Pekerjaan dalam dunia kerja harus dikerjakan secara fleksibel oleh individu dan tim, oleh karena itu perawat dirumah sakit harus mampu menjalankan OCB yang baik.Tujuan: Menguji pengaruh karakteristik individu dan kepuasan kerja terhadap komitmen organisasi, pengaruh karakteristik individu dan kepuasan kerja serta komitmen organisasi.Metode: Menggunakan analisa model structural equation modeling, dan dilakukan di RSUD Cut Meutia Lhokseumawe Aceh Utara.   jumlah sampel 120 perawat dengan teknik sampling metode simple random sampling.Hasil: Ditemukan karakteristik individu dan kepuasan kerja berpengaruh signifikan terhadap komitmen organisasi, karakteristik individu dan kepuasan kerja serta  komitemen organisasi berpengaruh signifikan terhadap OCB. Peran komitmen organisasi sebagai variabel intervening  memediasi hubungan karakteristik individu dan kepuasan kerja terhadap OCB.